IMPACT OF ORGANOPHOSPHATE PESTICIDE ROGOR ON BIOCHEMICAL PARAMETERS OF FRESHWATER CATFISH Clarias magur (HAMILTON, 1822) - KALITA, EVARANI; DEVI, KEERTI; SULTANA, NEHA; BAYAN, JIJNYASHA; TAMULI, HIMAKSHI (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
Pesticides are not only dangerous to the environment, but also hazardous to a person's health. Studies on pesticides have clearly established their link to cancer, Alzheimer's Disease, ADHD, birth defects and many more. Rogor is one of the organophosphates extensively used in agricultural practice. It is highly soluble in water for which it can easily enter into the nearby water sources and affect aquatic organisms. In the present study we have planned to observe the effects of rogor in some biochemical parameters in freshwater cat fish Clarias magur. Based on the LC50, we used two sub-lethal concentrations of Rogor - 1/5th (i.e; 13 mg/L) and 1/10th (i.e; 6.5mg/L) in our experiment. After 7 consecutive days of treatment, we have observed a dose dependent decrease in protein, glycogen and lipid content in both liver and muscle of the treated fishes. The amount of protein, glycogen and lipid was decreases with the increasing concentration of the rogor and the results were significant at 0.1 (P<0.1). The amount of blood glucose and total blood cholesterol was also decreases with increasing concentration of rogor.